North Korea's fait accompli: Implications of the changing status quo on the Korean Peninsula - Eric J. Ballbach (Stiftung Wissenschaft und Politik (SWP), 2022)
While the world's attention is focused on Russia's war against Ukraine and the intensifying conflict between the US and China, the security situation on the Korean Peninsula has continued to deteriorate. North Korea is steadily advancing the expansion of its military capabilities and recently undertook significant changes in its nuclear doctrine. At the same time, the rapidly changing geopolitical context makes a resolution of the North Korean nuclear conflict even less likely. North Korea's unilateral change of the status quo on the Korean Peninsula poses a serious challenge to the international community, which has few options to counter this threat that is far too dangerous to ignore.
Keywords: 320; Russia; war against Ukraine; Korean Peninsula; security; geopolitical context; Taiwan; China; nuclear weapons; deterrence; Indo-Pacific; Treaty on the Non-Proliferation of Nuclear Weapons (NPT)